Children treated for medulloblastoma and supratentorial primitive neuroectodermal tumor in Norway from 1974 through 2013: Unexplainable regional differences in survival. Issue 10 (1st July 2019) - Stensvold, Einar; Myklebust, Tor Åge; Cappelen, Johan; Due‐Tønnessen, Bernt J.; Due‐Tønnessen, Paulina; Kepka, Aleksandra; Johannesen, Tom Børge; Krossnes, Bård; Lundar, Tryggve; Maric, Snezana; Miletic, Hrvoje; Moholdt, Viggo; et al.
Abstract: Background: A previous study based on Norwegian Cancer Registry data suggested regional differences in overall survival (OS) after treatment for medulloblastoma (MB) and supratentorial primitive neuroectodermal tumor (CNS‐PNET) in Norway. The purpose of the present study was to confirm in an extended cohort whether there were regional differences in outcome or not, and if so try to identify possible explanations. Material and methods: Data from patients aged 0–20 years diagnosed with and treated for MB/CNS‐PNET at all four university hospitals in Norway from 1974 to 2013 were collected and compared. Results: Of 266 identified patients, 251 fulfilled inclusion criteria. MB was diagnosed in 200 and CNS‐PNET in 51 patients. Five‐year OS and event‐free survival (EFS) were 59% and 52%, respectively. There was a significant difference in five‐year OS and EFS between MB and CNS‐PNET patients; 62% versus 47% ( P =  0.007) and 57% versus 35% ( P <  0.001). In multivariable analysis, two factors were found to significantly contribute to improved five‐year OS and EFS, whereas one factor contributed to improved five‐year OS only. Gross total resection (GTR) versus non‐GTR (hazard ratio [HR] 0.53, P =  0.003; HR 0.46, P <  0.001) and cerebrospinal irradiation (CSI) versus non‐CSI (HR 0.24, P <  0.001; HR 0.28, P  < 0.001) for both, and treatment outside Oslo University Hospital for OS only (HR 0.64, P =  0.048). Conclusion: Survival was comparable with data from other population‐based studies, and the importance of GTR and CSI was confirmed. The cause for regional survival differences could not be identified.